Biochemical and Functional Interaction of Disrupted-in-Schizophrenia 1 and Amyloid Precursor Protein Regulates Neuronal Migration during Mammalian Cortical Development - Young-Pearse, Tracy L. (Society for Neuroscience, 2010)
Although clinically distinct, schizophrenia and Alzheimer's disease are common and devastating disorders that profoundly impair cognitive function. For Alzheimer's disease, key mechanistic insights have emerged from genetic studies that identified causative mutations in amyloid precursor protein (APP) and presenilin. Several genes have been associated with schizophrenia and other major psychoses, and understanding their normal functions will help elucidate the underlying causes of these disorders. One such gene is disrupted-in-schizophrenia 1 (DISC1). DISC1 and APP have been implicated separately in cortical development, with each having roles in both neuronal migration and neurite outgrowth. Here, we report a previously unrecognized biochemical and functional interaction between DISC1 and APP. Using in utero electroporation in the living rat brain, we show that DISC1 acts downstream of APP and Disabled-1 to regulate cortical precursor cell migration. Specifically, overexpression of DISC1 rescues the migration defect caused by a loss of APP expression. Moreover, knockdown of APP in cultured embryonic neurons results in altered subcellular localization of DISC1. Using transfected cells and normal brain tissue, we show that APP and DISC1 coimmunoprecipitate and that the intracellular domain of APP interacts with the N-terminal domain of DISC1. Based on these findings, we hypothesize that the APP cytoplasmic region transiently interacts with DISC1 to help regulate the translocation of DISC1 to the centrosome, where it plays a key role in controlling neuronal migration during cortical development.